Analisis Pragmatik Gaya Bahasa Hiperbola Dalam Iklan Kosmetik Anti-Aging - Ni Putu Isha Aprinica; Arik Agustina; Luh Eka Susanti; Ida Ayu Gayatri Kesumayathi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze the use of hyperbole in anti-aging cosmetic advertisements from a pragmatic perspective. Hyperbole is a form of linguistic expression frequently used in advertising to attract audience attention and form strong perceptions of a product. The main focus of this study is how hyperbole is used strategically in conveying advertising messages and influencing consumer behavior. The data in this study consist of anti-aging cosmetic advertisement texts collected from various media, including print, television, and digital platforms. Data collection techniques were carried out through documentation and observation of advertising content that emphasizes the use of hyperbole. The results of the study indicate that there are four dominant types of hyperbole in anti-aging cosmetic advertisements. First, temporal hyperbole, which emphasizes the speed of results, such as the claim "younger-looking skin in just 3 days." Second, quantitative hyperbole, which uses excessive numbers and percentages, for example "eliminates 99% of wrinkles instantly." Third, qualitative hyperbole, which exaggerates the efficacy or superiority of a product, such as "the secret to unparalleled eternal beauty." Fourth, comparative hyperbole, which compares a product with an unrealistic analogy or metaphor. From a pragmatic perspective, the use of hyperbole has three main functions, namely: (1) a persuasive function, to convince consumers that the product is very effective; (2) an emotive function, to arouse consumers' emotions and desires for an ideal appearance; and (3) a conative function, to encourage real action in the form of purchasing the product. This study confirms that hyperbole is not only a rhetorical device, but also a powerful communicative strategy in shaping consumer perceptions and behavior in the realm of cosmetic advertising.